Critical Religious Education (CRE) in practice: evaluating the reception of an introductory scheme of work. Issue 2 (4th May 2018) - Goodman, Angela
Abstract: Critical Religious Education (CRE) is a contemporary pedagogy of religious education developed by Andrew Wright and various colleagues over the past two decades. There has been widespread academic discourse about the pedagogy in theory but increasingly commentators have called for examples of it in practice. Over the past seven years a writing group associated with The Forum of Religious and Spiritual Education at King's College London have been developing practical materials aimed at supporting teachers in embedding the pedagogy in practice. Of particular relevance to this paper is the development of an introductory scheme of work, aimed at year 7 students, which has been trialled in a number of schools in and around London. In 2013, focus group interviews took place in four of these schools in order to ascertain the reception that the materials had received. The data suggests a very positive response to the introductory scheme of work and the CRE approach in general, partially dispelling some criticisms levelled at it in academic discourse. The author has thus suggested that the approach and the work of the writing group need further exposure, especially in schools, at conferences and on initial teacher education programmes.